2023
DOI: 10.1021/acsaem.3c01827
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Hydrogen Evolution Reaction Evaluation of CoNi(Cr/V) Medium-Entropy Alloys in an Acidic Environment

Shahbaz Ahmad,
Mehmet Egilmez,
Ramasamy Shanmugam
et al.

Abstract: Developing nonprecious metal-based electrocatalysts with outstanding performance has been the focal point of the scientific community for the past decade. Multiprinciple element medium-and high-entropy alloys have recently been known to exhibit a range of superior mechanical, physical, electrocatalytic, and anticorrosive properties, which are superior to traditional alloys. In this study, the electrocatalytic properties of equiatomic single-phase medium-entropy alloy electrodes with equiatomic compositions CoN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…The 2000th LSV polarization curve shifted slightly toward the positive potential side with a slight change in the onset potential compared with the first curve. The oxidation potentials and corresponding current responses for nickel­(II) oxidation in both curves are almost similar to the overpotentials at a current density of 10 mA cm –2 . However, the overpotential at 50 mA cm –2 for the 2000th curve is 525 mV vs RHE with a slight loss in the OER potential by ca.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…The 2000th LSV polarization curve shifted slightly toward the positive potential side with a slight change in the onset potential compared with the first curve. The oxidation potentials and corresponding current responses for nickel­(II) oxidation in both curves are almost similar to the overpotentials at a current density of 10 mA cm –2 . However, the overpotential at 50 mA cm –2 for the 2000th curve is 525 mV vs RHE with a slight loss in the OER potential by ca.…”
Section: Resultsmentioning
confidence: 58%
“…In addition, the double-layer capacitance of complex 4 (1.23 mF cm −2 ) was lower than that of the 4b composite (2.11 mF cm −2 ), which is probably due to the formation of stable π−π and synergetic interactions between the coumarin ring of the complex 4 and MWCNTs, while other composites displayed similar capacitance values as that of the bare complex. 40 However, the overpotential at 50 mA cm −2 for the 2000th curve is 525 mV vs RHE with a slight loss in the OER potential by ca. 2.2% with a Δη 50 of 11 mV vs RHE.…”
Section: Morphology Studies Of the Complex Compositementioning
confidence: 99%
“…This technique of 3D printing and laser ablation can be extended to a broad range of photoactive materials for fabricating nanostructured photoelectrodes. Figure shows the developmental path of stable photocatalytic systems and electrode fabrication methods with an aim to achieve the highest solar energy conversion efficiency. …”
Section: Research Trends and Conclusionmentioning
confidence: 99%
“…However, this process suffers from high energy requirements and the production of CO 2 , which cause further environmental issues. Recently, electrocatalytic water splitting for efficient production of H 2 has been considered a propitious solution for achieving a clean energy system. , It has been shown that noble metals like Pt, Ru, and Pd can be used as the best choices for catalysis of the hydrogen evolution reaction (HER) due to their high current density and low overpotential . In order to achieve low-cost catalysts while maintaining high efficiency, some noble metal-free systems, like metal phosphides, , chalcogenides, , oxides and alloys, have been introduced in recent years. However, there is still great research attention to develop and design new efficient and low-cost electrocatalysts for the HER process.…”
Section: Introductionmentioning
confidence: 99%